SYSTEMS AND METHODS FOR SOLVING PROBLEMS - Kuklin, Volodymyr; Shapovalova, Olena; Sirenka, Tetiana (European Science, 2025)
The review considers existing methods of solving problems and systems implementing these processes. Examples of strict problem solving using equations obtained from first principles and tested by long-term practice are given. The concept of constructing a